Bio-functional azithromycin loaded polyvinyl alcohol and fucoidan hydrogel coating for titanium Implants: An experimental in vitro study - Maria Sharon Velraj; Arvina Rajasekar (Journal of Oral Biology and Craniofacial Research, 2025)
Background: Titanium-based implants are widely used in biomedical applications due to their superior mechanical properties and biocompatibility. However, the risk of postoperative infections and inadequate osseointegration remains a significant challenge. Hydrogels, with their tunable properties, offer a promising approach for enhancing the bioactivity of titanium surfaces. This study explored the development and characterization of an azithromycin-loaded PVA-fucoidan hydrogel coating on titanium and evaluated its physicochemical and biological properties. Aim: To fabricate and characterize an azithromycin-loaded PVA-fucoidan hydrogel coated on titanium surfaces and assess their antibacterial, hemocompatibility, and biocompatibility properties. Materials and methods: Commercially pure ASTM grade V titanium disks (n = 25) were prepared and treated via radio frequency argon plasma. PVA-fucoidan hydrogel was synthesized and loaded with azithromycin (1 % w/w), followed by electrophoretic deposition onto the titanium surface. Surface characterization was performed using Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), atomic force microscopy (AFM), and contact angle measurements. In-vitro drug release was analyzed using UV–Vis spectrophotometry. Antibacterial efficacy was tested against Streptococcus mutans and Escherichia coli (n = 3 per group). Hemocompatibility and cytotoxicity were evaluated via hemolysis assay, MTT assay, and live/dead cell assay (n = 3 replicates per assay). Results: FTIR confirmed the successful integration of azithromycin without altering the hydrogel structure. SEM and AFM revealed uniform, textured coatings with enhanced roughness. Contact angle measurements indicated improved hydrophilicity (58°). Sustained azithromycin release was observed. The azithromycin-loaded coating exhibited superior antibacterial activity, larger inhibition zones, excellent hemocompatibility (0.8 % hemolysis), and 100 % cell viability in fibroblast cultures. Conclusion: Azithromycin-loaded PVA-fucoidan hydrogel coating on titanium demonstrated promising physicochemical and biological properties, making it a potential candidate for enhancing the performance of titanium-based biomedical implants.